The archaeology of ancestors : death, memory, and veneration - Hill, Erica; Hageman, Jon B., 1967-; McAnany, Patricia Ann (University Press of Florida, 2016)
Ancient peoples used their ancestors' perceived influence to deal with domestic disputes, advertise wealth, validate authority, and much more. Erica Hill and Jon Hageman's volume explores these dimensions of ancestor worship through the study of documentary evidence and material remains, including funerary structures, human remains, art and iconography, structured deposits, and architecture.